Miniaturization Design for 8 × 8 Butler Matrix Based on Back-to-Back Bilayer Microstrip - Yu Zhai; Xiaoxing Fang; Kejia Ding; Fei He (International Journal of Antennas and Propagation)
A low-cost, compact 8 × 8 Butler matrix based on a novel bilayer microstrip configuration is presented and implemented for 4.3 GHz telecommunication application. A back-to-back placed bilayer microstrip structure has been proposed to avoid using crossover. To expand operational bandwidth of the Butler matrix, a three-branch line directional coupler has been employed as 3 dB/90° bridge, and a kind of improved two-order Schiffman phase shifter has been adopted as fixed phase shifter. For application of indoor wireless communication, a compact broadband 8 × 8 Butler matrix has been designed and fabricated. The measured results show that the return loss of the matrix is lower than −10 dB, the isolation is better than 17 dB, the power distribution error is less than ±2.0 dB, the phase error is less than ±15°, and the relative bandwidth is more than 23%.